2019
DOI: 10.1002/anie.201901384
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Intrinsic Catalytic Activities of Single‐Gold‐Nanoparticle‐Based Enzyme Mimetics

Abstract: Gold nanoparticles (AuNPs) have been demonstrated to serve as effective nanomaterial‐based enzyme mimetics (nanozymes) for a number of enzymatic reactions under mild conditions. The intrinsic glucose oxidase and peroxidase activities of single AuNPs and Ag–Au nanohybrids, respectively, were investigated by single NP collision electrochemical measurements. A significantly high turnover number of nanozymes was obtained from individual catalytic events compared with the results from the classical, ensemble‐averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 60 publications
3
57
0
Order By: Relevance
“…Stochastic collision electrochemistry has emerged as a unique methodology to study one entity at a time, which may be a cell, a vesicle, a nanoparticle, etc [8–23] . Some typical works based on stochastic electrochemistry have been reported by fluidizing particles collision with the conventional electrode [24] and single gold nanoparticle (Au NPs) collision with the ultramicroelectrode [25] . A carbon ultramicroelectrode (C‐UME, diameter of ∼6.8 μm) is immersed into an electrolyte solution containing freely diffusing Au NPs, the collision of a single Au NP with C‐UME at a bias potential triggers the catalytical oxidation of glucose in the presence of O 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stochastic collision electrochemistry has emerged as a unique methodology to study one entity at a time, which may be a cell, a vesicle, a nanoparticle, etc [8–23] . Some typical works based on stochastic electrochemistry have been reported by fluidizing particles collision with the conventional electrode [24] and single gold nanoparticle (Au NPs) collision with the ultramicroelectrode [25] . A carbon ultramicroelectrode (C‐UME, diameter of ∼6.8 μm) is immersed into an electrolyte solution containing freely diffusing Au NPs, the collision of a single Au NP with C‐UME at a bias potential triggers the catalytical oxidation of glucose in the presence of O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…According to sticking model, the theoretical slope of linear plot of concentration vs. frequency is 0.025 s −1 fM −1 . In this condition, Pd NPs are assumed to be irreversibly sticked on the C‐UME surface at a diffusion limited flux of NPs [25,34,35] . Also, the theoretical slope is 4.14 s −1 fM −1 , if the stochastic events are governed by random walk model, where Pd NPs collide and ultimately desorb from the C‐UME surface (Supporting Information Section S6) [34] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Moreover, H 2 O 2 is one of the most common products of enzyme catalyzed oxidations, thus a series of metabolites including glucose, cholesterol, uric acid, and sarcosine could be converted to H 2 O 2 quantitively with corresponding oxidases or enzyme mimetics. 18 For example, in Amplex Red Glucose/Glucose Oxidase assay, glucose could be oxidized to glucuronolactone in the presence of glucose oxidase and oxygen, and one equivalent of H 2 O 2 is produced and quantied by Amplex Red in this process. However, this resulting uorescence could be bleached by extra amounts of H 2 O 2 in presence of horseradish peroxidase (HRP), and Amplex Red is also vulnerable to photo oxidation.…”
Section: New Assay Development Based On Hkperox-redmentioning
confidence: 99%
“…The electrocatalytic amplification (ECA) method developed by Bard's group in 2007 was considered as a powerful analytical method in which nanoparticles can catalyze a specific electrochemical reaction collide with an inert microelectrode, opening the possibility of exploring the relationship between structure, agglomeration, and activity of catalytic particles unambiguously ( Xiao and Bard, 2007 ). Long et al applied ECA to accurately characterize the intrinsic catalytic activity of single Au NPs as glucose-like oxidases and single Ag–Au nanohybrids as peroxidase-like enzymes ( Hafez et al, 2019 ). Compton et al revealed the electrocatalytic oxidation mechanism and kinetics of hydrazine (N 2 H 4 ) by using graphene oxide platelets randomly decorated with palladium nanoparticles (Pd/GO) as collision objects ( Miao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%